Fińskie internaty w dwudziestowiecznej Laponii. Wpływ obowiązku szkolnego i polityki asymilacyjnej na saamskich uczniów oraz ich tożsamość kulturową - Oleńska, Agnieszka (Etnografia. Praktyki, Teorie, Doświadczenia, 2023)
In my work, I will present the history of the indigenous Saami people living in Finland. After World War II, forced education and boarding schools became one of the tools of discrimination against indigenous peoples. Children aged 6 or 7 were sent to institutions as far as one hundred kilometers from home. Growing up outside the natural environment, where a foreign language was used and the Saami identity was leveled, meant that entire generations of Saami people lost the knowledge of the language of their ancestors. I will describe how the traumatic events that took place in boarding schools shaped the psyche and self-esteem of young Saami people and what impact it had on the further fate of Saami communities. In my work, I will present the history of the indigenous Saami people living in Finland. After World War II, forced education and boarding schools became one of the tools of discrimination against indigenous peoples. Children aged 6 or 7 were sent to institutions as far as one hundred kilometers from home. Growing up outside the natural environment, where a foreign language was used and the Saami identity was leveled, meant that entire generations of Saami people lost the knowledge of the language of their ancestors. I will describe how the traumatic events that took place in boarding schools shaped the psyche and self-esteem of young Saami people and what impact it had on the further fate of Saami communities. In my work, I will present the history of the indigenous Saami people living in Finland. After World War II, forced education and boarding schools became one of the tools of discrimination against indigenous peoples. Children aged 6 or 7 were sent to institutions as far as one hundred kilometers from home. Growing up outside the natural environment, where a foreign language was used and the Saami identity was leveled, meant that entire generations of Saami people lost the knowledge of the language of their ancestors. I will describe how the traumatic events that took place in boarding schools ...